2011
DOI: 10.1007/dcr.0b013e318208b90f
|View full text |Cite
|
Sign up to set email alerts
|

A New Antimesenteric Functional End-to-End Handsewn Anastomosis: Surgical Prevention of Anastomotic Recurrence in Crohn's Disease

Abstract: The Kono-S anastomosis appears to be effective in preventing anastomotic surgical recurrence in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(164 citation statements)
references
References 19 publications
2
137
0
2
Order By: Relevance
“…Dr. Kono has named this new anastomosis an antimesenteric functional end-to-end hand-sewn anastomosis, or Kono-S anastomosis. Initial reports indicate that the endoscopic recurrence rate at 3 and 12 months after surgery is lower than after a side-toside functional end anastomosis [5]. These initial observations were confirmed by another prospective observational study [6].…”
mentioning
confidence: 80%
“…Dr. Kono has named this new anastomosis an antimesenteric functional end-to-end hand-sewn anastomosis, or Kono-S anastomosis. Initial reports indicate that the endoscopic recurrence rate at 3 and 12 months after surgery is lower than after a side-toside functional end anastomosis [5]. These initial observations were confirmed by another prospective observational study [6].…”
mentioning
confidence: 80%
“…A recent study conducted by Kono [6] showed the novel anastomotic technique (Kono-S anastomosis) focusing on rationale for the recurrence site, anastomotic susceptibility to mechanical distortions, and preservation of blood supply and innervation. It revealed that Kono-S anastomosis was superior to standard anastomoses such as, handsewn end-to-end or side-to-side anastomosis with a single layer of continuous absorbable sutures, or stapled functional end-to-end anastomosis concerning endoscopic recurrence score and surgical recurrence at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The mesentery proper or mesocolon was divided at the mesenteric edge of the bowel wall using vessel-sealing system (Liga​Sure system, Valleylab, Boulder, CO) to avoid unnecessary devascularization and denervation of residual intestine [6] (fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no anastomotic technique has been proven to be superior in reducing surgical recurrence rates in this setting. In 2003 a new combined stapled and hand-sewn antimesenteric functional end-to-end anastomosis (Kono-S anastomosis) was designed to minimize surgical recurrence [2]. In this video report, we describe our technique for performance of a new antimesenteric functional end-to-end handsewn (Kono-S) anastomosis [3] (Video S1).…”
mentioning
confidence: 99%